2006
DOI: 10.1007/s10729-006-7666-7
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive analysis of average productivity among health maintenance organizations, 1985 to 2001

Abstract: This paper examines the evolution of average productivity among HMOs for 4,419 Health Maintenance Organizations (HMOs) from 1985 to 2001. For both IPA and non-IPA HMOs, HMO productivity increased from 1990 to 1996 and rapidly decreased from 1997 to 2001. In contrast to cost functions that show scale economies for IPA and non-IPA HMOs, production functions showed scale economies for IPA HMOs were constant and non-IPA HMOs having only slight scale economies. This suggests that much of the scale economies observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…The HMO data come from InterStudy census data (InterStudy 1985–1987, 1988–2001) and Group Health Association HMO Directories (Group Health Association of America 1989–1992). The InterStudy data are used to form county‐level measures of HMO penetration and the number of HMOs following the methodology of Wholey, Engberg, and Bryce (2006). County‐level market measures come from the Area Resource File (ARF, Bureau of Health Professions 1999).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HMO data come from InterStudy census data (InterStudy 1985–1987, 1988–2001) and Group Health Association HMO Directories (Group Health Association of America 1989–1992). The InterStudy data are used to form county‐level measures of HMO penetration and the number of HMOs following the methodology of Wholey, Engberg, and Bryce (2006). County‐level market measures come from the Area Resource File (ARF, Bureau of Health Professions 1999).…”
Section: Methodsmentioning
confidence: 99%
“…The HMO data come from InterStudy census data (InterStudy 1985(InterStudy -1987(InterStudy , 1988(InterStudy -2001 and Group Health Association HMO Directories (Group Health Association of America 1989America -1992. The InterStudy data are used to form county-level measures of HMO penetration and the number of HMOs following the methodology of Wholey, Engberg, and Bryce (2006 HSA measures were constructed by first measuring HMO enrollment, ARF characteristics, and wage data at the county level. The ARF provided county-level measures of the number of primary care physicians, median percapita income, unemployment rate, population of the HSA, and percent of the population over 65 years of age.…”
Section: Datamentioning
confidence: 99%
“…Schramm (2001) and Town et al (2004) both reported that conversion of HMO plans to for-profit status does not result in demonstrable economic efficiency in the health plans. Wholey et al (2006), in a descriptive analysis of HMO plans between 1985 and 2001, even found for-profit HMOs to be less productive than not-for-profit plans. Shen and Melnick (2004) directly tested whether for-profit HMOs exert more financial pressure than not-for-profit plans on hospital cost and revenue growth between 1989 and 1998.…”
Section: Effect Of Hmo Penetrationmentioning
confidence: 99%
“…Some argue that FP health plans are no more effective than nonprofit plans at improving health system efficiency (Weisbrod 1988), which is empirically supported by Schramm (2001) and Town, Feldman, and Wholey (2004). Yet Wholey, Engberg, and Bryce (2006) found FP HMOs to be less productive than not‐FP plans between 1985 and 2001. Shen and Melnick (2004) found that, between 1989 and 1998, hospital costs and revenues grew at a slower rate in higher FP HMO share areas, especially in high HMO penetration areas.…”
Section: Conceptual Frameworkmentioning
confidence: 99%